(untitled) (Journal of the College of Education for Women, 2019)
The research aims to develop alternatives to transportation at the entrance to the Educational City (University of Baghdad) during the morning and evening peaks, which result from of the traffic congestion at the entrances to the educational city (the University of Baghdad), and affects the emotional, functional, and social performance of the whole city, and leads to hotbeds of confluence and congestion at the entrances in the morning and evening peaks. This movement was measured on the ground for pedestrians and vehicles. Some criteria were adopted to determine the density of road length to the area and density of roads for the number of users and the rate of the area served by roads. The research reviews the experiences of some countries to solve the problem of overcrowding and the application of their standards and its applications to the problem of research to determine the correctness with the study case. The use of spatial data and the construction of a database through geographic information systems (GIS) software enables a spatial analysis to select temporary functional alternatives for these entrances to ensure easier and smoother traffic in the study area, as well as proposals for some theoretical alternatives. One of the most important findings of the research that the Education City needs additional double functional entrances and exits.